Al-Khṭāb al-Ḥubbī fī at-Turātha al-: Arabīy: al-falsafīy wa al-kalāmīy wa al-taṣwufīy wa al-a’dabīy. - Zam-Zam Afandi Abdullah (Al-Jami'ah Research Centre, 2001)
ln intellectual tradition of Islam, Philosophy, Theology, Sufism, besides Arts had been developed rapidly. Almost all human problems become their object of study. Among them is problem of love that is rarely studied. This article tries to study problem of